Perceptions of diabetes in rural areas of Eastern Uganda - Elizeus Rutebemberwa; Sheila K. Katureebe; Sheba N. Gitta; Amos D. Mwaka; Lynn Atuyambe (AOSIS, 2013)
Background: People diagnosed with diabetes mellitus are increasing in sub-Saharan Africa and prompt care seeking depends on perceptions of the illness. Objective: The objective was to explore perceptions of diabetes in rural areas. Method: We conducted a qualitative, explorative and descriptive study in rural eastern Uganda. Eight focus group discussions with community members were conducted. Community members were presented with a story about a person with diabetes symptoms and their perceptions of the diagnosis and treatment elicited. Four focus group discussions with people with diabetes and seven key informant interviews with health workers were conducted. Respondents were asked how the community interpreted symptoms of diabetes, its causes and whether it was curable. Manifest content analysis was used. Results: Some respondents thought people with diabetes symptoms had HIV or were bewitched. Causes of diabetes mentioned included consuming too much fatty food. Some respondents thought diabetes is transmitted through air, sharing utensils with or sitting close to people with diabetes. Some respondents thought that diabetes could heal fast whilst others thought it was incurable. Conclusion: Misdiagnosis may cause delay in seeking proper care. Preventive programmes could build on people's thinking that too much fatty food causes diabetes to promote diets with less fat. The perception of diabetes as a contagious disease leads to stigmatisation and affects treatment seeking. Seeing diabetes as curable could create patient expectations that may not be fulfilled in the management of diabetes. Rural communities would benefit from campaigns creating awareness of prevention, symptoms, diagnosis and management of diabetes.